2010
DOI: 10.2341/09-008cr
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Performance of Vital Bleaching Techniques

Abstract: Tooth bleaching results obtained with different techniques (home bleaching, in-office bleaching with or without light source and a combination of in-office bleaching + home bleaching) were similar after a two-week period. Dentists must inform their patients about the expected outcomes of each procedure and provide an evidence-based choice. SUMMARY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(97 citation statements)
references
References 21 publications
(41 reference statements)
2
87
1
Order By: Relevance
“…We asked the participants to keep a daily record of whether they experienced TS by using a 5-point verbal numeric rating scale 4,30,31 and a visual analog scale. 3,12,32 For the numeric rating scale, we instructed the participants to choose 1 score from 0 to 4 to represent the intensity of the TS, with 0 indicating no TS; 1, mild TS; 2, moderate TS; 3, considerable TS; and 4, severe TS. For the visual analog scale, we instructed the participants to place a line perpendicular to a line 10 mm long with 0 at one end indicating no TS and at the 10-mm end indicating unbearable TS.…”
Section: Original Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We asked the participants to keep a daily record of whether they experienced TS by using a 5-point verbal numeric rating scale 4,30,31 and a visual analog scale. 3,12,32 For the numeric rating scale, we instructed the participants to choose 1 score from 0 to 4 to represent the intensity of the TS, with 0 indicating no TS; 1, mild TS; 2, moderate TS; 3, considerable TS; and 4, severe TS. For the visual analog scale, we instructed the participants to place a line perpendicular to a line 10 mm long with 0 at one end indicating no TS and at the 10-mm end indicating unbearable TS.…”
Section: Original Contributionsmentioning
confidence: 99%
“…18 These components cause dental discoloration because of their dark hue and ability to adhere to dental surfaces. 19 The concern about bleaching in smokers also is highlighted by the eligibility criteria of several clinical trials on bleaching, which exclude smokers, [2][3][4]6,10,13,[20][21][22] without scientific support that smoking can jeopardize the bleaching outcome.…”
mentioning
confidence: 99%
“…A number of clinical trials have compared the performance of higher and low-concentrated agents used for home or inoffice tooth bleaching and the majority has showed a similar whitening effect for both concentrations and techniques (inoffice or at-home). 5,11,[13][14][15] Nevertheless, the incidence of tooth sensitivity or irritation gingival is more common when the agent concentration is increased. 7,13 Few studies have evaluated the longevity of the whitening effect for more than 1 year after treatment.…”
Section: Introductionmentioning
confidence: 98%
“…5,11,[13][14][15] Nevertheless, the incidence of tooth sensitivity or irritation gingival is more common when the agent concentration is increased. 7,13 Few studies have evaluated the longevity of the whitening effect for more than 1 year after treatment. 7,[16][17][18] Besides, there is a lack of randomized clinical trials that verify the patients' perception about the treatment' longevity or the influence of possible factors associated to dietary habits in the shade relapse.…”
Section: Introductionmentioning
confidence: 98%
“…4,10 Different light sources can be used to activate bleaching agents such as halogen, plasma arc lamp, LED, and lasers (argon, diode, KTP, Nd:YAG, CO 2 , etc) or a combination. [11][12][13][14] Various studies have shown different tooth color changes following bleaching. Kiomars et al evaluated 2 different wavelengths of diode laser (λ = 810 nm and λ = 980 nm) for teeth color changes.…”
Section: Comparison Of Tooth Color Change After Bleaching With Convenmentioning
confidence: 99%